1987
DOI: 10.1063/1.98413
|View full text |Cite
|
Sign up to set email alerts
|

Electron trap center generation due to hole trapping in SiO2 under Fowler–Nordheim tunneling stress

Abstract: The relation between generation of neutral electron trap centers and hole trapping in thermally grown SiO2 under Fowler–Nordheim tunneling stress has been investigated. The experimental results show that the density of neutral electron trap centers is proportional to the density of trapped holes under Fowler–Nordheim tunneling stress with various electric fields and the total number of electrons injected into the oxide. The generation mechanism is explained by a model based on strained bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 15 publications
0
13
0
3
Order By: Relevance
“…32,33 Second, based on Fig. 12, we can speculate the existence of an amphoteric defect which is filled with an electron near threshold, is empty and thus neutral near flatband, and can be filled with a hole ͑devoid of an electron͒ during stress when high-energy holes are available.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…32,33 Second, based on Fig. 12, we can speculate the existence of an amphoteric defect which is filled with an electron near threshold, is empty and thus neutral near flatband, and can be filled with a hole ͑devoid of an electron͒ during stress when high-energy holes are available.…”
Section: Discussionmentioning
confidence: 96%
“…First, previous studies of hot-hole damage in SiO 2 point to the generation of electron neutral traps. 32,33 Although we are cautious about the physical interpretation of the fitting parameter 0 used here as a capture cross section, FIG. 13.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the generation of electron traps is enhanced by hole injection [4], and is proportional to the number of trapped holes [ 2 ] . Although some theoretical investigations have been carried out on the microscopic origin of hole traps and electron traps, the mechanism of generation of these traps, and the relationship between the hole traps and electron trap generation have not been fully clarified so far.…”
Section: Introductionmentioning
confidence: 99%
“…В ряде работ [8][9][10][11] при достаточно высоких зарядах туннельной инжекции электронов (Q in j > 0.1 Кл/см 2 ) и напряженности электрического поля (E > 8 МВ/см) после введения положительного заряда наблюдалось образование отрицательного заряда, который авторы объясняли генерацией новых электронных ловушек. Было предложено несколько механизмов их генерации [8][9][10][11][12][13][14][15][16]. В работах [10,12] генерация электронных ловушек у катода связывалась с освобождением водорода вблизи анода под действием горячих электронов, его миграцией к катоду и взаимодействием водорода с оборванными связями оксидных ловушек вблизи катода.…”
Section: Introductionunclassified